Stability of Jensen-Type Functional Equations on Restricted Domains in a Group and Their Asymptotic Behaviors. (12th September 2011) - Chung, Jae-Young; Kim, Dohan; Rassias, John Michael
Abstract : We consider the Hyers-Ulam stability problems for the Jensen-type functional equations in general restricted domains. The main purpose of this paper is to find the restricted domains for which the functional inequality satisfied in those domains extends to the inequality for whole domain. As consequences of the results we obtain asymptotic behavior of the equations.